Symposium 6: On Phenomenography and Researching Online Tutor Support - Watland, Philip A. (Proceedings of the International Conference on Networked Learning, 2006)
Rapid developments of affordable information and communication technologies are seen as assisting a shift in pedagogy attitudes from a teacher-centred/content orientation to a student-centred/learning orientation, and combined with the various forms of technology-mediated interaction, influencing the roles and experiences for both online tutors and students. Within this context, there have been calls from researchers (Gibson, 2003; McCartan, 2000) to address the need of understanding the student’s perspective in technology-supported education settings. This paper contributes to the debate on how to understand and research the described experiences students give to phenomenon and aims to present the potential contribution of the phenomenographic approach (Marton, 1981; Marton & Booth 1997) for researching networked management learning phenomena on a theoretical and empirical level by connecting this theoretical discussion with current research on students experiences of online tutor support. Discussion of the considerations of using a phenomenographic approach within the context of this research is highlighted in this paper.